2022
DOI: 10.1155/2022/9204201
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Bioinformatics and Clinical Correlation Analysis of Key Genes, Pathways, and Potential Therapeutic Agents Related to Diabetic Nephropathy

Abstract: Background. Diabetic nephropathy (DN) is a common microvascular complication of diabetes and a major cause of end-stage renal disease, resulting in a substantial socioeconomic burden around the world. Some unknown biomarkers, mechanisms, and potential novel agents regarding DN are yet to be identified. Methods. GSE30528 and GSE1009 were downloaded as training datasets to identify differentially expressed genes (DEGs) of DN. Common DEGs were selected for further analysis. Gene Ontology and Kyoto Encyclopedia of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In addition, NPHS1 is an essential slit diaphragm protein and plays and important role in the development and function of glomerular filtration barrier. Jiang et al reported that the abundance of NPHS1 was downregulated in DN and significantly positively correlated with eGFR. , In addition, the integrated analysis of mRNA expression profiles and clinical characteristics have identified many hub genes underlying DN, including the ECM components of COL1A1, FN1, COL6A3, COL1A2, THBS2, CD44, TNC, LUM, and POSTN, and the complement-related genes of C1q, C3, C7, CLU, and CFH, and these hub genes have also been proved to play crucial functions in the pathological process of DN at protein levels. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NPHS1 is an essential slit diaphragm protein and plays and important role in the development and function of glomerular filtration barrier. Jiang et al reported that the abundance of NPHS1 was downregulated in DN and significantly positively correlated with eGFR. , In addition, the integrated analysis of mRNA expression profiles and clinical characteristics have identified many hub genes underlying DN, including the ECM components of COL1A1, FN1, COL6A3, COL1A2, THBS2, CD44, TNC, LUM, and POSTN, and the complement-related genes of C1q, C3, C7, CLU, and CFH, and these hub genes have also been proved to play crucial functions in the pathological process of DN at protein levels. …”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al reported that the abundance of NPHS1 was downregulated in DN and significantly positively correlated with eGFR. 25,26 In addition, the integrated analysis of mRNA expression profiles and clinical characteristics have identified many hub genes underlying DN, including the ECM components of COL1A1, FN1, COL6A3, COL1A2, THBS2, CD44, TNC, LUM, and POSTN, and the complement-related genes of C1q, C3, C7, CLU, and CFH, 27−29 and these hub genes have also been proved to play crucial functions in the pathological process of DN at protein levels. 30−33 The other 788 differentially expressed mRNA-protein pairs (70%, 788/1152) showed poor or even negative correlation, which indicated that there were complex regulatory mechanisms in DN to controlling the abundance of mRNA and protein, including mRNA stability and decay, translation efficiency, and protein degradation, particularly post-transcriptional regulation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In our model, FF age-independently elevated the renal levels of VEGFA protein, despite decreased Vegfa mRNA after low-dose FF, suggestive of post-transcriptional mechanisms of regulation. Using bioinformatics tools, FF has been previously predicted to increase VEGFA expression in diabetic nephropathy [ 39 ], while the drug has been shown to increase VEGFA levels in the visceral adipose tissue of FF-treated normolipemic rabbits [ 40 ]. Moreover, in both young and old rats in our model, low-dose FF inhibited the expression of Serpine1 , activated by HIF-1 under hypoxic conditions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the database used in this work is commonly utilized in other bioinformatics studies. Some scholars have identified VEGFA, NPHs1, WT1, CTGF, SYNPO and POD XL as promising biomarkers to diagnose DKD using GSE30528 and GSE1009 databases ( 44 ). Others used GSE30528 database and WGCNA method to identify six key genes related to DKD ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…There has been evidence that changes in the HNF1B gene contribute to a slight predisposition to type 2 diabetes, Possibly caused by mutations in the HNFB1 gene that create a protein that is incapable of binding DNA or fails to transactivate DNA following binding ( 71 ). It is clear from these evidences that key genes are important in the pathogenesis of DKD, as well as potential diagnostic and therapeutic targets ( 44 , 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%